2002
DOI: 10.1128/jvi.76.8.3965-3973.2002
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of Virus-Specific B Lymphocytes in Germinal Centers of Simian-Human Immunodeficiency Virus-Infected Rhesus Monkeys

Abstract: The etiology of the lymphadenopathy and follicular hyperplasia associated with human immunodeficiency virus type 1 (HIV-1) infection has remained unclear. To determine whether the B-lymphocyte expansions characteristic of this syndrome represent polyclonal and virus-specific processes, the antigen specificity of B cells in lymphoid tissues of monkeys infected with simian-human immunodeficiency virus (SHIV) chimeras was assessed using an inverse immunohistochemical assay with biotinylated HIV-1 envelope gp120 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 50 publications
3
14
0
Order By: Relevance
“…In previous studies of SHIV-infected rhesus monkeys, we have shown that lymphoid GCs formed during primary and chronic immunodeficiency virus infection include a high frequency of Envspecific B cells (42). In the present report, we extend those studies with an analysis of Ig sequences from Env-binding GCs.…”
supporting
confidence: 55%
See 3 more Smart Citations
“…In previous studies of SHIV-infected rhesus monkeys, we have shown that lymphoid GCs formed during primary and chronic immunodeficiency virus infection include a high frequency of Envspecific B cells (42). In the present report, we extend those studies with an analysis of Ig sequences from Env-binding GCs.…”
supporting
confidence: 55%
“…Subject Mm18284 was infected with SHIV-KB9ct, and subject Mm19941 was infected with SHIV-KB9(Ϫ305). Some immunologic and virologic data from these monkeys have been previously reported (42,45,47). Infection of both animals was confirmed by serologic and virologic assays (45,47).…”
Section: Shiv Clones Animal Infections and Sample Handlingmentioning
confidence: 84%
See 2 more Smart Citations
“…GCs have been shown to be occupied by virus-specific and nonspecific B cells in SHIV 89.6P infection (20). Thus, the severe loss of proliferating B cells in GCs observed in the Mamu-A‫10ء‬ Ϫ monkeys may have caused the substantial loss of general B-cell immunity that has been documented for HIV-1 and SIV infection (6,22).…”
Section: Discussionmentioning
confidence: 98%